Problematika Stay At Home Pada Anak Usia Dini Di Tengah Pandemi Covid 19 - M.Pd, A. Tabi'in (Universitas Hamzanwadi, 2020)
The emergence of covid-19 virus in Indonesia affects the activities of children who have to stay at home to prevent widespread transmission of the virus. Children who originally did free activities outside the home are now inversely proportional they have to move inside the house. This research is based on the problematic of children staying at home, studying at home, playing at home and any activities carried out at home during the pandemic period. This study aims to determine the problems that arise in children who come to stay silent at home or stay at home. Children basically cannot be silent because this is an explorative or explorer period. The method used in this research is a descriptive qualitative approach with data collection techniques using interviews, observation, and documentation. After that it is processed through data triangulation. Based on the research findings of Puspita Subah Kindergarten children experiencing some problems when staying at home, the problems include, Stress, heightened sensitivity, temper tantrums, spoiled/not independent and behavioral disorders